2005
DOI: 10.1080/15476910490916044
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene Does Not Accelerate Autoimmune Diabetes in NOD Mice

Abstract: Pre-existing or contributing risk factors, including genetic predisposition and environmental influences, are largely thought to play a crucial (though ill-elucidated) role in the development of autoimmunity. Trichloroethylene (TCE) is a widely used organic solvent, which has been suspected of increasing the prevalence of autoimmune diseases, e.g., lupus, following environmental contamination. Although few epidemiological data are available, several studies reported an accelerated and more severe disease in TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…A previous study found that TCE exposure did not exacerbate autoimmunity in NOD.ShiLtJ mice (Ravel et al, 2005). In agreement, exposure to TCE had no effect on profibrogenic gene expression or hepatic collagen deposition in NOD.ShiLtJ mice, suggesting that exposure to this environmental contaminant selec-tively modifies the progression of liver disease only in the context of autoimmunity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A previous study found that TCE exposure did not exacerbate autoimmunity in NOD.ShiLtJ mice (Ravel et al, 2005). In agreement, exposure to TCE had no effect on profibrogenic gene expression or hepatic collagen deposition in NOD.ShiLtJ mice, suggesting that exposure to this environmental contaminant selec-tively modifies the progression of liver disease only in the context of autoimmunity.…”
Section: Discussionsupporting
confidence: 72%
“…Early fibrosis was reported to occur in only a small number of NOD.c3c4 mice (Irie et al, 2006), rendering the observation that TCE exacerbates this feature of disease quite exciting. Of importance, TCE exposure did not cause fibrosis in livers of NOD.ShiLtJ mice, in which TCE has been shown to not increase autoimmunity (Ravel et al, 2005). Taken together, the results in NOD.c3c4 mice suggest that TCE has the potential to act as a disease modifier in the presence of concurrent hepatic autoimmunity.…”
Section: Discussionmentioning
confidence: 68%
“…At the present time, there is little scope to screen for xenobiotics which promote hypersensitivity and/or autoimmunity. A few animal models of autoimmune diseases have been developed, such as the non-obese diabetic (NOD) mouse (Atkinson and Leiter, 1999;Ravel et al, 2004) or the Bio-Breeding (BB) rat (Kroemer et al, 1992) for type 1 diabetes, and the (NZB £ NZW) F 1 mouse (Burnett et al, 2004;Ravel et al, 2002), for systemic lupus erythematosus. Their use in developmental or juvenile studies would be extremely problematic, owing to the compromised reproductive capacity of the animal strains used.…”
Section: Future Directions For Pre-clinical Testing: Hypersensitivitymentioning
confidence: 99%
“…Rather, this highlights a model-specific response and the importance of defining the impact of TCE on autoimmunity across multiple models. Interestingly, in nonobese diabetic (NOD) mice, which also develop autoimmunity, TCE exposure did not accelerate autoimmunity and the mice did not develop autoimmune hepatitis (Ravel et al, 2005). In NOD mice, TCE exposure reduced lymphocyte proliferation and cytokine production, suggesting a protective effect (Ravel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%